Aspects of purine and pyrimidine metabolism - Black, Duncan Arthur (Division of Chemical Pathology, 2017)
In Chapter 1 a review of the literature concerning aspects of erythrocyte membrane transport and metabolism, and purine and pyrimidine metabolism is presented. The effects of pH, pO₂ and inorganic phosphate (Pi) on the uptake and metabolism of hypoxanthine by erythrocytes has been studied in Chapter 2. Uptake of hypoxanthine and accumulation of inosine 5'-monophosphate (IMP) were markedly increased at acid pH, high external phosphate concentrations, and low pO₂. Release of accumulated IMP as hypoxanthine occurred at alkaline pH values and low external phosphate concentrations. Conditions favouring IMP accumulation gave rise, in the absence of hypoxanthine, to a corresponding increase in 5'-phosphoribosyl-1-pyrophosphate (PRPP). Intracellular phosphate concentrations were markedly pH dependent and a model is presented whereby hypoxanthine uptake and release are controlled by intracellular concentrations of inorganic phosphate and 2,3- bisphosphoglycerate (2,3-DPG). These allosteric effectors influence, in opposing ways, two enzymes governing IMP accumulation, namely PRPP synthetase and 5'-nucleotidase. These metabolic properties suggest that the erythrocyte could play a role in the removal of hypoxanthine from anoxic tissue. In Chapter 3 the kinetics and mechanism of transport of orotate across the human erythrocyte membrane and the effect of pH and inorganic phosphate on its metabolism (in the erythrocyte) have been studied. It has been shown that orotate enters erythrocytes with non-saturable kinetics and with a capacity of 190 μmoles/1 packed cells/min at a concentration of 4-6 mmolar. The presence of competition for transport by a number of anions and the lack of competition by uridine is indicative of transport by a general anion transporter, with the ability for concentrative uptake in the absence of other external anions being compatible with transport via a ping-pong mechanism. Inhibition of transport by the specific band 3 inhibitors DIDS and CHCA confirm that transport is via the band 3 anion transporter. This explains the lack of significant uptake of orotate by most differentiated tissues which lack the intact band 3 protein. However, the demonstration of band 3 in rat hepatocytes (Cheng and Levy, 1980) provides a mechanism for the orotate transport which has been observed in liver (Handschumacher and Coleridge, 1979). Changes in pH and inorganic phosphate (Pi) concentrations have been shown to have marked effects on the relative quantities of metabolic products produced by the erythrocyte from orotate. There was an increase in orotate metabolised with increasing Pi, an effect augmented by lowering the pH, and most easily explained by the allosteric activation of PRPP synthetase by Pi. The increase in UTP levels with decreasing pH may be the consequence of both increased PRPP availability for the formation of uridine nucleotide from orotate, and decreased conversion of UMP to uridine by pyrimidine 5'-nucleotidase, which is known to be inhibited by phosphate. The accumulation of UDP sugars is optimal at a phosphate concentration of 10 mmolar, which is unexplained but would be compatible with an inhibitory effect of Pi on CTP synthetase. A PRPP wasting cycle at alkaline pH values is proposed to explain the apparent paradox where no PRPP was observed to accumulate in erythrocytes (Chapter 2) at pH values of 7.6 and above in the presence of 10 mmolar phosphate and no added hypoxanthine, yet the metabolism of orotate, which is a PRPP utilising reaction, at alkaline pH values was readily demonstrable here. This (apparent paradox) can be resolved if one assumes that even in the absence of added hypoxanthine and demonstrable intracellular IMP there are sufficient quantities of hypoxanthine and/or IMP to maintain a PRPP wasting cycle at alkaline pH values. The cycle is interrupted at acidic pH values as phosphate levels rise and inhibit 5'-nucleotidase, an effect augmented by the decreasing levels of 2,3-DPG which accompany decreasing pH. This wasting cycle has recently been confirmed by P. Berman (unpublished). The kinetics of orotate uptake by erythrocytes and its eventual release as uridine provides a role for the erythrocyte in the transport and distribution of pyrimidines to peripheral tissues. A model is proposed and involves the de novo production of orotate in the liver. In the next step erythrocytes take up the orotate secreted by the liver into the circulation, convert it into an intermediate buffer store of uridine nucleotides, whose distribution is a function of pH and phosphate concentration, and eventually release it as uridine, which is a readily available form of pyrimidine for utilisation by peripheral nucleated cells. The enhancement of uptake of labelled orotate into nucleic acids of cultured cells is demonstrated here. The degradative half of the cycle proposes that uracil and palanine are the predominant degradative forms of pyrimidines produced by peripheral cells, and their ultimate metabolic fate is complete catabolism in the liver to CO₂ and water. In the final chapter the possible role of the human erythrocyte in the prevention of reperfusion injury has been investigated. The development of a model of renal ischaemia in the rat is described. The ability of human erythrocytes, "primed" by preincubating in acid medium of high Pi concentration and low pO₂, to take up hypoxanthine in a concentrative manner when perfused through ischaemic rat kidney is demonstrated. Attempts to demonstrate improved survival and renal function in rats with "primed" human erythrocytes prior to reperfusion were, however, unsuccessful. It is further demonstrated that "unprimed" human erythrocytes, resident in ischaemic rat kidney for 3 hours, take up hypoxanthine and convert it to IMP. that erythrocytes could play a physiological prevention of reperfusion injury.